Bifenthrin Causes Kidney Damage via Induction of Oxidative Stress, Activation of Pro-Inflammatory Cytokines, and Up-Regulation of Apoptosis in Wistar Rats - Ujong, Ujong Peter; Ibor, Mbang Edet (Darul Yasin Al Sys, 2024)
This study investigated the role of oxidative stress, inflammation, and apoptosis in bifenthrin-induced kidney damage in Wistar rat models. Adult male rats (110-300g) were divided into three groups of 10 rats each. Group 1 served as the normal control, while groups 2-3 were orally given 1 mg/ kg body weight bifenthrin for 14 and 28 days respectively. The results revealed that bifenthrin administration caused a significant (p<0.05) decrease in renal antioxidant enzymes such as superoxide dismutase, catalase, glutathione, glutathione S-transferase, and glutathione peroxidase. Conversely, malondialdehyde levels were significantly (p<0.05) increased. Pro-inflammatory cytokines TNF-α, IL1-β, IL-6, COX-2, iNOS, LTE B4, and PGE2 were significantly (p<0.05) elevated, highlighting an inflammatory response. Additionally, the apoptotic markers, caspase-3, and BAX were significantly (p<0.05) increased, while BCL-2, an anti-apoptotic protein, was significantly (p<0.05) decreased, indicating enhanced apoptosis. Renal function markers, creatinine, and urea were also significantly (p<0.05) elevated in bifenthrin-induced groups. Furthermore, the histopathology results revealed morphological damages in the kidneys of groups 2 and 3 animals These findings demonstrate bifenthrin's potential to cause significant oxidative stress, inflammation, apoptosis, and structural damage in renal tissues.